2021
DOI: 10.1002/aic.17163
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing catalyst supports at single catalyst pellet and packed bed reactor levels: A comparison study

Abstract: Using a catalyst support with optimal pore network and pellet structures is critical to the success of an industrial heterogeneous catalyst. This work optimizes the catalyst support of a dry reforming of methane catalyst at packed bed reactor level, that is, effects of concentration and temperature gradients in the reactor are accounted for. Meanwhile, the optimization at reactor level is also compared with that at single catalyst pellet level where fixed concentrations and temperature are imposed on the pelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…For example, the diffusion fluxes on the external surface of catalyst pellets are used as source terms for the mass balance equations at the reactor level; the concentrations in the reactor are set to be the boundary conditions for the mass balance equations at the pellet level. A similar approach is also successfully employed in our previous works. ,, …”
Section: Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the diffusion fluxes on the external surface of catalyst pellets are used as source terms for the mass balance equations at the reactor level; the concentrations in the reactor are set to be the boundary conditions for the mass balance equations at the pellet level. A similar approach is also successfully employed in our previous works. ,, …”
Section: Modelingmentioning
confidence: 99%
“…A similar approach is also successfully employed in our previous works. 22,25,26 2.1. Reaction Kinetics.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical modeling demonstrated that the multichannel cylinder-shaped catalyst support could achieve high effectiveness, low pressure drop, and excellent heat transfer performance, as compared to sphere-shaped, cylinder-shaped, or single-channel cylinder-shaped catalysts . Besides, it was reported that a four-channel cylinder-shaped catalyst had the highest methane conversion in the practical DRM test among different shaped catalysts (e.g., sphere, cylinder, trilobe, Raschig ring, and four-channel cylinder) . Due to its high thermal and mechanical stability and strong interaction with Ni nanoparticles, , Al 2 O 3 is commonly used as a support for Ni-based catalysts for the DRM reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Partopour and Dixon investigated the impact of pellet shape on the catalyst performance on a reactor scale by numerically generating fixed beds and found that the pellet shape significantly affected the conversion of methanol in partial oxidation. Liu et al optimized the catalyst pellet shape and pore size for the dry reforming of methane on both pellet and packed bed reactor levels and reported an overestimated catalyst performance at the pellet level compared with the estimation at the reactor level. However, few publications have optimized the catalyst shape on a reactor scale, especially for liquid-phase reactions up to now.…”
Section: Introductionmentioning
confidence: 99%